A multimethod examination of the relationship between coaching behavior and athletes` inherent self-talk - Zourbanos, N.; Hatzigeorgiadis, A.; Tsiakaras, N.; Chroni, S.; Theodorakis, Y. (Journal of Sport & Exercise Psychology, 2010)
The aim of the present research was to investigate the relationship between coaching behavior and athletes` inherent self-talk (ST). Three studies were conducted. The first study tested the construct validity of the Coaching Behavior Questionnaire (CBQ) in the Greek language, and provided support for its original factor structure. The second study examined the relationships between coaching behavior and athletes` ST in field, with two different samples. The results showed that supportive coaching behavior was positively related to positive ST (in one sample) and negatively related to negative ST (in both samples), whereas negative coaching behavior was negatively related to positive ST (in one sample) and positively related to negative ST (in both samples). Finally, the third study examined the relationships experimentally, to produce evidence regarding the direction of causality. The results showed that variations in coaching behavior affected participants` ST. Overall, the results of the present investigation provided considerable evidence regarding the links between coaching behavior and athletes` ST and suggested that coaches may have an impact on athletes` thoughts.